HEALTH TOURISM POTENTIALS IN THE NORTHWEST REGION OF IRAN EMPHASIZING LAKE URMIA - Fatemeh Aghapour Maleki , Siavash Imeni Gheshlagh , Ali Safari Ajab Shir (PalArch's Journal of Archaeology of Egypt / Egyptology, 2021)
Lake Urmia is quite possibly the main secured worldwide park, which has been exceptionally respected because of its restorative properties as hydrotherapy and sludge therapy from the removed past up to this point and draws in vacationers consistently. Nonetheless, because of the absence of a legitimate tourism foundation, offices, and administrations, just as the absence of appropriate data on social, monetary, and actual improvements around here, it has not been considered notwithstanding the presence of numerous potential and real limits corresponding to health tourism. Consequently, this study was directed to explore the advancement possibilities of health tourism in the lake. This exploration depends on a blend of particular analyses, narrative, and field techniques, which have been utilized because of the applied idea of the examination. The statistical population of this examination incorporates the tourism activists and the tourism specialists. To break down the interior and external parts of the climate utilizing the Delphi method (as an open questionnaire), a semi-structured interview was directed with 16 specialists dealing with lake undertakings, and afterward, the Swat matrix was finished by gauging the cases thinking about the suppositions and answers of the significant specialists. The results show that the sludge of Lake Urmia is free from contamination and has useful components for the body. Likewise, the consequences of analyzing interviews, perceptions, assessments, and regard for the appropriate infrastructure facilities demonstrate that the massive and economical possibility and the field of making plans and ventures for therapeutic-coastal tourism exist in the northwest district of Iran. Focusing on the sludge therapy project will help extend health tourism objectives in the northwest area of Iran. The results likewise showed that because of the presence of all three components of water, salt, and sludge as a rich source of treatment in Lake Urmia, the foundation of a center of the hydrotherapy, halotherapy, and sludge therapy, and the improvement of health tourism in Lake Urmia are conceivable and lastly it leads to the advancement of health tourism and thus to the financial and social advancement of this locale.